Arliss Cutter : Bone Rattle - Book 3 - Cameron, Marc (Thorndike, Maine : Center Point Large Print, 2021)
Pulled from their duties to keep track of sequestered jurors in a high-profile trial involving a massive drug conspiracy, Arliss Cutter and deputy Lola Teariki realize that they are dealing with something much bigger, and darker, than a simple drug trial when the prosecuting attorney is murdered.
Keywords: United States marshals -- Fiction; Murder -- Investigation -- Alaska; Fiction; Alaska -- Fiction; Detective and mystery fiction; Thrillers (Fiction)